L’immaginario labirintico nel romanzo quebecchese: dal mito classico al labirinto contemporaneo - De Luca, Ylenia (Oltreoceano - Rivista sulle migrazioni, 2021)
La lettura dell’erranza nel romanzo quebecchese evidenzia la presenza di un labirinto universale nel quale si iscrivono altri labirinti. La fondazione del Québec, il suo passato hanno influenzato la scrittura creando immaginari labirintici evidenti in molti romanzi quebecchesi contemporanei. The Labyrinthine Imagination in the Québec Novel: From the Classic Myth to the Contemporary Labyrinth The representation of travel in the works of Québec writers reveals the presence of a universal labyrinth in which other labyrinths are inscribed. The labyrinthine imagination which surfaces in many contemporary novels is linked both to the foundation of Québec and its past marked by colonization, the relationship with France and the proximity with the United States.